Genetic evolution analysis of PRRSV ORF5 gene in five provinces of Northern China in 2024 - Yanyin Jian; Chun Lu; Yuan Shi; Xiangyu Kong; Jun Song; Jintao Wang (BMC Veterinary Research)
Abstract Background Porcine reproductive and respiratory syndrome (PRRS) was first discovered in North America in 1987, and since then it has been spread widely all over the world. The prevalence of PRRS has caused significantly economic losses to pig industry in many countries. Objectives Investigate the prevalence and genetic evolution of porcine reproductive and respiratory syndrome virus (PRRSV) in five provinces of northern China. Methods 190 samples suspected of PRRS were collected from 28 pig farms in five provinces of northern China. The PRRSV ORF7 and ORF5 gene were detected by RT-PCR, and the ORF5 gene were sequenced for the homology and genetic evolution analysis. Results The positive samples of ORF7 gene were 50, and its positive rate was 26.32%. The positive samples of ORF5 gene were 48, and its positive rate was 25.26%. The sequenced results of the ORF5 gene showed that 48 positive samples all belonged to PRRSV-2. Among them, 26 samples were NADC34-like strains, 17 samples were NADC30-like strains, and 5 samples were classical strains. The amino acid sequence analysis of PRRSV GP5 indicated that there was a deletion at the 37th amino acid in 4 NADC30-like strains. The amino acids of the transmembrane region 1 in all positive strains are relatively conserved, and multiple amino acid mutations were observed in the signal peptide, transmembrane region 2, and B cell epitope. The amino acid mutations were different in different strains and regions. The above results demonstrated that the complexity and diversity of PRRSV genetics. Conclusion The strains from lineage 1 became the dominant strains in five provinces of northern China in 2024. The positive rate of NADC34-like strains was the highest in Heilongjiang Province and the NADC30-like strains were the most prevalent in these regions. The genetic evolution of PRRSV presented a complex trend. This study provided the data support for understanding PRRSV variation and for PRRS prevention and control in five provinces of northern China.